Healthcare professionals’ knowledge, attitudes, and practices regarding China’s National Centralized Drug Procurement policy: a cross-sectional study in Shaanxi Province - Shen, Qian; Kang, Limin; Ye, Dan; Li, Youjia; Zhang, Kanghuai (Frontiers in Public Health, 2025)
BackgroundSince 2019, the Chinese government has been fully implementing the National Centralized Drug Procurement (NCDP) policy, with the core objective of reducing drug costs and alleviating the medical burden on patients. As the practitioners of this policy, healthcare professionals (HCPs) play a crucial role in its implementation. Therefore, it is necessary to evaluate their knowledge, attitudes, and practices (KAP) regarding the implementation of the (NCDP) policy and the factors influencing these aspects.MethodsWe conducted a cross-sectional online survey on HCPs from public hospitals in Shaanxi Province from 2022 August to September. A structured self-administered questionnaire was used to collect data on demographics, knowledge of NCDP, attitude toward NCDP policy, and practice of policy implementation. KAP adequacy was dichotomized at the 70% cut-off (Knowledge: adequate vs. inadequate, Attitude: positive vs. negative; Practice: good vs. poor). All the variables were descriptively analyzed, and multivariate logistics regression analysis was used to explore the factors associated with KAP level.ResultsA total of 1,257 valid responses were received. Of these, 58.4% demonstrated adequate knowledge, 63.2% held positive attitudes, and 35.2% exhibited good practices. Significant occupational disparities emerged, with pharmacists outperforming physicians across all KAP domains (p < 0.01). Multivariate logistic regression analysis showed that professional title, being a pharmacist, and attending the training were independently associated with adequate knowledge. Positive attitudes were significantly associated with 11–20 years of working experience, having a bachelor’s degree, being a pharmacist, and attending training. Proactive practice was associated with longer working years, being a pharmacist, and training attendance. The main concerns of HCPs regarding the NCDP policy were guaranteeing medicine quality (93.2%), strengthening clinical outcomes research (80.0%), and strengthening monitoring of adverse reactions (79.6%).ConclusionOur study found that HCPs in Shaanxi Province possessed a moderate level of knowledge and generally positive attitudes toward the NCDP policy, yet demonstrate room for enhanced practice. Pharmacists play a pivotal role in policy implementation. To strengthen HCPs’ policy endorsement and ensure faithful implementation, targeted training on therapeutic effectiveness and safety evaluation is essential, as it can alleviate clinical concerns and bridge the gap from evidence to actionable competence. Future research should concentrate on generating high-quality clinical evidence, analyzing long-term policy impacts, identifying implementation barriers, and designing educational interventions to bolster HCPs’ knowledge and positive attitudes regarding the NCDP policy.